Uji Aktivitas Farmakologi Ekstrak Daun Jambu Air (Syzygium Samarangense)Terhadap Mencit (Mus Musculus) - Resky Aulifiyah Haswari B; Nur Sahra; Masnaeni Thamrin; Silvia Astuti; Diva Sukrianingsih; Nurul Nisai; Nur Alya Nazifa; Alya Salsabila; Andi Utari Prasetya Ningrum (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
This study aims to determine the pharmacological activity profile of water apple (Syzygium samarangense) leaf extract on male mice (Mus musculus) and to observe the effect of increasing doses on its pharmacological classification. The screening method involved observing 25 parameters, including behavioral, autonomic, and motoric responses, using three concentration levels: 1%, 2%, and 4%. The results showed that the extract exhibited diverse pharmacological effects, with the Central Nervous System (CNS) stimulation and CNS depression being the most prominent activities at a 1% concentration. Interestingly, as the concentration increased, specific effects like parasympathomimetic activity remained consistently significant across all doses (ranging from 18.29% to 21.46%). The observed parasympathomimetic effects such as increased urination and defecation suggest that the extract may promote intestinal motility and bladder contraction. Additionally, the presence of sympathomimetic and parasympatholytic activities indicates a complex interaction with the autonomic nervous system. In conclusion, Syzygium samarangense leaf extract possesses potential as a parasympathomimetic agent, which could be further investigated for treating hypertension through vasodilation or as a diuretic and digestive aid. Further specific testing is required to isolate the active compounds responsible for these effects.